THE ROLE OF MUSIC THERAPY IN THE DEVELOPMENT OF PSYCHOLOGICAL PROTECTION MECHANISMS IN PRESCHOOL CHILDREN (IN THE CONTEXT OF FAMILY PSYCHOLOGY) (Universal International Scientific Journal, 2026)
Music therapy in preschool children is an effective tool for developing psychological defense mechanisms, reducing stress, and increasing emotional stability. Musical activities with parents help strengthen the mental stability of children. The thesis highlights the pedagogical and practical significance of music therapy in the context of family psychology.
Keywords: Preschool age; Psychological defense mechanisms; Music therapy